Chicken CH25H inhibits ALV-J replication by promoting cellular autophagy - Xie, Tingting; Feng, Min; Zhang, Xi; Li, Xiaoqi; Mo, Guodong; Shi, Meiqing; Zhang, Xiquan (Frontiers in Immunology, 2023)
Autophagy plays an important role in host antiviral defense. The avian leukosis virus subgroup J (ALV-J) has been shown to inhibit autophagy while promoting viral replication. The underlying autophagic mechanisms, however, are unknown. Cholesterol 25-hydroxylase (CH25H) is a conserved interferon-stimulated gene, which converts cholesterol to a soluble antiviral factor, 25-hydroxycholesterol (25HC). In this study, we further investigated the autophagic mechanism of CH25H resistance to ALV-J in chicken embryonic fibroblast cell lines (DF1). Our results found that overexpression of CH25H and treatment with 25HC promoted the autophagic markers that microtubule-associated protein 1 light chain 3 II (LC3II) and autophagy-related gene 5(ATG5), while decreased autophagy substrate p62/SQSTM1 (p62) expression in ALV-J infection DF-1 cells. Induction of cellular autophagy also reduces the levels of ALV-J gp85 and p27. ALV-J infection, on the other hand, suppresses autophagic marker protein LC3II expression. These findings suggest that CH25H-induced autophagy is a host defense mechanism that aids in ALV-J replication inhibition. In particular, CH25H interacts with CHMP4B and inhibits ALV-J infection in DF-1 cells by promoting autophagy, revealing a novel mechanism by which CH25H inhibits ALV-J infection. Although the underlying mechanisms are not completely understood, CH25H and 25HC are the first to show that autophagy inhibits ALV-J infection via a new enzyme activity-independent mechanism.